The champion of urban water resources management in the Chinese city — the case of Ningbo - Chan, Faith Ka Shun; Zhu, Fangfang; Li, Lei; Lu, Miran; Tang, Yu-Ting; Griffiths, James (2020)
Ningbo is a coastal megacity located at the East Coast of China and developing rapidly with proactive trading and export economic activities. The city owns a ranked top ten international port and it is the major strategic spot of 21st century maritime Silk Road from the “Belt and Road” policy established for promoting further international trades and developments. In future, populations and economy in Ningbo are expected continuously growing in the next few decades. The demand of quality freshwater resources thus is enormously increasing. Ningbo municipal government has established the “Five water management” (五水共治) policy in 2013 that aims to manage (i) sewage discharge; (ii) flooding; (iii) surface water; (iv) water conservation and (v) freshwater supply. Indeed, the municipal government also liaised and initiated the “Sponge City Program” after 2015 that Ningbo was selected as one of the pilot city; these policies and practices are successful up to now. This article adopts the case study of Ningbo to investigate the reasons of municipal government to promote the policy, to understand the public perception of this water management policy in Ningbo through conducted semi-structured interviews. During the 2017 and 2019, we conducted a questionnaire (N = 110) and interviews (N = 10) that follow up for justification of the public perception with the local communities. Our findings indicated that the communities had not been engaged closely with these practices, but generally supporting these two urban water management practices; and agreed that the urban water conditions (urban floods and pollution) had been improved. Also, the article discusses whether these (5 Water and SCP) practices can be extensively applied in other Chinese cities. We will provide recommendations at the end of the article.